2002
DOI: 10.1002/1521-3765(20020315)8:6<1269::aid-chem1269>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Three-Coordinate [CuIIX3]− (X=Cl, Br), Trapped in a Molecular Crystal

Abstract: Mixtures of [Ph3PNPPh3]+Cl− with CuBr2 (or CuBr2+CuCl2) in ethanol/dichloromethane yield crystals containing three‐coordinate copper(II) with mixed chloride and bromide ligands, namely [Ph3PNPPh3]+[CuCl0.9Br2.1]− (1) and [Ph3PNPPh3]+[CuCl2.4Br0.6]− (2). The trigonal‐planar coordination of copper(II) is angularly distorted but unambiguous, as there is no other halide ligand within 6.7 Å of the copper atom. Density functional theory (DFT) calculations on planar [CuClBr2]− show that the energy surface for angle b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 14 publications
(27 reference statements)
1
11
0
1
Order By: Relevance
“…The compound is isostructural with the analogous bis(triphenylphosphine)iminium hexachlorocuprate [30]. The geometrical parameters of the bis(triphenylphosphine)iminium cation is consistent with those observed in the literature.…”
Section: Resultssupporting
confidence: 84%
“…The compound is isostructural with the analogous bis(triphenylphosphine)iminium hexachlorocuprate [30]. The geometrical parameters of the bis(triphenylphosphine)iminium cation is consistent with those observed in the literature.…”
Section: Resultssupporting
confidence: 84%
“…28 We discovered that crystallisation of mixtures of copper(II) with chloride and bromide ligands, and the Ph 3 28 The crystal packing follows the general principles described above. We further showed that solvent is influential in this crystallisation, because crystallisations from ethanol without dichloromethane yielded instead the more familiar compounds (Ph 3 PNPPh 3 …”
Section: Trapping Unusual Three-coordinate Cu(ii) As [Cux 3 ]mentioning
confidence: 93%
“…Network 2[Cu]Ge was swelled with acetonitrile in a cuvette to form a gel that could be analysed by UV/Vis spectroscopy. The spectrum of the purple gel revealed a maximum absorption wavelength in the yellow region ( λ max =549 nm), which corresponded to the purple [CuBr 4 ] 2− anion and a shoulder in the red region ( λ =628 nm), which corresponded to the green [CuBr 3 (MeCN)] − anion (Figure ) . Despite the paramagnetic anions, the 31 P NMR chemical shift was observed and did not change from that of 2[Br]Ge , and the IR spectrum confirmed that the aryl groups on the germanium centres were still present.…”
Section: Resultsmentioning
confidence: 99%